KULTUR JARINGAN KUNIR PUTIH (Kaempferia rotunda L.) - Djadja Siti Hazar Hoesen (BERITA BIOLOGI, 1998)
Shoot cultures of Kaempferia rotunda L.were established from rhizome segment.In the 1st experimen these explants were planted on Gamborg/B5 medium that supplemented with BA concentrations were (0, 0.5, 1 and 2) mg/l and/or kinetine were (0, 2 and 4) mg/l.In 2nd experiment these explants planted in Murashige and Skoog medium (MS).This medium supplemented with BA concentrations (0, 2 and 4) mg/l and/or NAA (0 and 1) mg/l.The result in the 1st experiment showed that the best proliferated shoots was from the culture that supplemented with BA 1 mg/l and kinetine 4 mg/l, while in the 2nd experiment the best proliferated shoots was from the culture that supplemented with BA 4 mg/l and NAA 1 mg/l.These shoots were then subcultured on MS liquid medium supplemented with BA (5 mg/l) and MS agar medium was supplemented with BA (2 mg/l) + 2iP (0.5 mg/l) + thidiazuron (0.01 mg/l) + NAA (0.5 mg/l).The cultures could induce the shoots number and produce the morphological plantlets for acclimatization,and acclimatization successed on soil and compost mixed medium in ratio 1:1.